Australian and Japanese Value Stereotypes: A two Country Study - Soutar, Geoffrey N.; Grainger, Richard; Hedges, Pamela (Journal of International Business Studies, 1999)
Australians and Japanese working in Australian and Japanese organizations in both countries were involved in a research project that estimated stereotypical views of national culture. Respondents rated the importance of cultural values in Australia and Japan using the List of Values (LOV) instrument. The results of a discriminant analysis suggested that potentially detrimental misunderstandings about their respective cultures may exist between Australians and Japanese engaged in mutual international business.